Intervención optométrica en paciente masculino de 19 años con miopía magna y fotofobia atendido en la Óptica Científica Guaranda Sucursal Montalvo octubre 2024 - marzo 2025. - Acurio Paredes, Diana Anays (2025)
We present the case of a 19-year-old male patient who comes to the optometric office with symptoms of blurred distance vision and photophobia, which have negatively impacted his quality of life and daily productivity. Diagnosed with high myopia since the age of six, he has used corrective lenses, renewing them annually. However, in srecent years, his condition has worsened, and despite having had an examination nine months ago, the symptoms persist, especially after long hours in front of electronic devices. In addition, the patient reports headaches and difficulties driving at night. His medical history includes a family history of myopia and diabetes, suggesting a possible genetic predisposition. This case highlights the need for a thorough optometric evaluation and appropriate treatment to improve his vision and quality of life.